Keputusan Elektronis Pada Layanan Perizinan Pendirian Perguruan Tinggi Swasta (Studi Kasus Putusan PTUN Nomor 521/K/TUN/2018) - Fathin, Siti Labiba; Erliyana, Anna (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 10 No 4 (2021), 2021)
This study was conducted with a normative research that provides answers to two issues in this research, first, electronic decree regulation in the government administration law and omnibus law; second, analyzing the decisions of judges from the first level verdict to cassation verdict, related to electronic decree on licensing services for the establishment of private higher education at the Directorate General of Higher Education, Research, and Technology. Regarding the first issue, an answer was found that Electronic Decree are regulated in UUAP, especially Article 38 in conjunction with the Omnibus Law, where Electronic Decree have the same legal force or are not different from written decree. However, there is a change in the Omnibus Law regarding this electronic decree, namely the change occurs in the deletion of paragraphs 5 and 6 of Article 38, so that electronic decree no longer have to be made in writing, and there is an electronic system that is centralized in the central government. Regarding the second issue, the TUN verdict Number 53/B/2018/ PT.TUN.JKT, could not be implemented by the Kemenristekdikti because the judex facti of the Judges in the decision was wrong, and besides there was an ultra petita in the decree, so the Kemenristekdikti putted on appeal to the Supreme Court for the verdict of TUN Number 53/B/2018/PT.TUN.JKT. the Supreme Court granted the appeal and canceled the verdict of TUN Number 53/B/2018/PT.TUN.JKT Kajian ini dilakukan dengan penelitian normatif yang memberikan jawaban dua permasalahan dalam penelitian ini, pertama, pengaturan keputusan elektronis di undang-undang administrasi pemerintahan dan omnibus law; kedua, menganalisa putusan majelis hakim dari putusan tingkat pertama sampai dengan tingkat kasasi terkait keputusan elektronis pada layanan perizinan pendirian perguruan tinggi swasta di Direktorat Jenderal Pendidikan Tinggi, Riset, dan Teknologi. Terkait permasalahan pertama, ditemukan jawaban bahwa Keputusan Elektronis diatur di UUAP khususnya Pasal 38 juncto Omnibus Law, dimana Keputusan Elektronis mempunyai kekuatan hukum yang sama atau tidak berbeda dengan Keputusan tertulis. Namun, terdapat perubahan pengaturan dalam Omnibus Law mengenai keputusan elektronis ini, yaitu perubahan terjadi pada penghapusan ayat 5 dan ayat 6 dari Pasal 38, sehingga Keputusan elektronis, tidak lagi harus dibuat Keputusan tertulis, dan adanya sistem elektronis yang terpusat di pemerintah pusat. Terkait permasalahan kedua, putusan TUN Nomor 53/B/2018/ PT.TUN.JKT, namun putusan tersebut tidak dapat dilaksanakan oleh pihak Kemenristekdikti karena judex facti Majelis Hakim pada putusan tersebut telah keliru, dan adanya ultra petita dalam putusan tersebut, sehingga pihak Kemenristekdikti mengajukan permohonan kasasi ke Mahkamah Agung untuk putusan TUN Nomor 53/B/2018/ PT.TUN.JKT. Majelis Hakim Agung mengabulkan permohonan kasasi tersebut serta membatalkan putusan TUN Nomor 53/B/2018/PT.TUN.JKT.